2011
DOI: 10.1021/ol202973z
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Free Aromatic Nucleophilic Substitution of meso-Bromoporphyrins with Azide Anion: Efficient Synthesis and Structural Analyses of meso-Azidoporphyrins

Abstract: meso-Mono- or diazidoporphyrins were readily obtained in high yields by the catalyst-free aromatic nucleophilic reaction of the corresponding bromoporphyrins with azide anions under mild conditions. The molecular structures of the obtained azides were unambiguously determined by X-ray crystallographic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…To promote basic and applied studies into functionalized porphyrins, methods for their synthesis need to be simplified and standardized as much as possible, and not require special skills and high‐cost reagents. For this purpose, we recently established general, convenient, and facile methods for the preparation of meso ‐functionalized porphyrins . One of our key reactions is the nucleophilic aromatic substitution (S N Ar) reaction, which is a facile and efficient method for the introduction of a heteroatom substituent when electron‐deficient aromatic compounds need to be functionalized.…”
Section: Introductionmentioning
confidence: 99%
“…To promote basic and applied studies into functionalized porphyrins, methods for their synthesis need to be simplified and standardized as much as possible, and not require special skills and high‐cost reagents. For this purpose, we recently established general, convenient, and facile methods for the preparation of meso ‐functionalized porphyrins . One of our key reactions is the nucleophilic aromatic substitution (S N Ar) reaction, which is a facile and efficient method for the introduction of a heteroatom substituent when electron‐deficient aromatic compounds need to be functionalized.…”
Section: Introductionmentioning
confidence: 99%
“…[5,16] We have used this procedure to prepare (bacterio)chlorophyll mimics in which the two recognition groups of the zinc porphyrin are placed on the same side of the porphyrin macrocycle. [5,16] We have used this procedure to prepare (bacterio)chlorophyll mimics in which the two recognition groups of the zinc porphyrin are placed on the same side of the porphyrin macrocycle.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, we reported a catalyst‐free aromatic nucleophilic substitution reaction of meso ‐bromoporphyrin with azide anion . Keeping this unusual yet useful reaction in mind, we performed the reactions without Pd catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, we reported ac atalyst-free aromatic nucleophilic substitution reactiono fmeso-bromoporphyrinw ith azide anion. [17] Keepingt his unusual yet useful reaction in mind, we performed the reactions withoutP dc atalyst. Careful TLC analysis of the reactionm ixture indicated that this catalyst-free reaction stopped at the mono-substitution stage, for example, the reaction at 80 8Cf or 2h selectively afforded 4.T hen, Pd(dppf)Cl 2 ·CH 2 Cl 2 was added to this reaction mixture.…”
mentioning
confidence: 99%